Kekuatan genggam tangan, skor Child Pugh, dan massa otot pada pasien dengan sirosis hati - Amanda Trixie Hardigaloeh; Rino Alvani Gani; Irsan Hasan; Andri Sanityoso Sulaiman (Jurnal Gizi Klinik Indonesia, 2018)
Background: Malnutrition is independent factor related to morbidity, mortality and high cost of treatment in liver cirrhosis. Hand grip strength (HGS) is one of the method use for malnutrition detection and prognosis evaluation. The correlation of HGS with liver function (Child Pugh score) and muscle mass is controversial. These important evaluation is not yet avalaible in Indonesia.Objective: Aim of this study is to assess the role of HGS measurement in malnutrition and its correlation with liver function and muscle mass.Method: This is a cross-sectional study in liver cirrhosis patients at Hepatobiliary Clinic of Cipto Mangunkusumo Hospital from February to June 2015. Nutritional status was assessed by HGS. Muscle mass was obtained from bioimpedance. Data were analyzed using Spearman correlation test.Results: There were 115 patients liver cirrhosis at Hepatobiliary Clinic of Cipto Mangunkusumo Hospital, 112 patients who fit the inclusion criteria, consisted of 79 men and 33 women with mean age 54.15±10.55 years, median Child Pugh score 6 (5-13) with median HGS 26 (11-50) kgF, mean muscle mass 44.43±8.12 kg. The median intake of energy 1334.82 (604.75-3023.7) kkal, median protein 45.87 (19-114.5) gram. Prevalence of malnutrition according HGS was 33%. Hand grip strength is not correlated with Child Pugh score (p=0.046; r=-0.19) however it is correlated with muscle mass (p<0.00; r=0.70).Conclusion: There are 33% malnutrition cases based on HGS in out patient liver cirrhosis. There is no correlation between HGS with Child Pugh score however HGS is correlated with muscle mass in liver cirrhosis.